Associations between long-term exposure to ambient air pollution and Parkinson's disease prevalence: A cross-sectional study. (February 2020) - Salimi, Farhad; Hanigan, Ivan; Jalaludin, Bin; Guo, Yuming; Rolfe, Margaret; Heyworth, Jane S.; Cowie, Christine T.; Knibbs, Luke D.; Cope, Martin; Marks, Guy B.; Morgan, Geoffrey G.
Abstract: Background: Epidemiological studies have reported contradictory results regarding the effects of ambient air pollution on Parkinson's disease (PD). This study investigated the associations between long-term exposure to particulate matter <2.5 μm in diameter (PM2.5 ) and nitrogen dioxide (NO2 ) and PD among participants in the 45 and Up Study, which comprised adults older than 45 years living in New South Wales, Australia. Methods: We conducted a cross-sectional analysis of long-term exposure to PM2.5 and NO2 concentrations and prevalence of PD using data from around 240, 000 cohort members from the 45 and Up Study, NSW. Annual average concentrations of NO2 and PM2.5 were estimated at the participants' residential address using satellite-based land use regression models. Logistic regression was used to quantify the associations between these pollutants and ever physician-diagnosed PD, after adjusting for a range of individual- and area-level covariates. Results: Among the 236, 390 participants with complete data, 1, 428 (0.6%) reported physician-diagnosed PD. Annual mean PM2.5 and NO2 concentrations for the cohort were 5.8 and 11.9 μg m −3, respectively, and were positively, but not statistically significantly associated with PD. The odds ratio for a 1 μg m −3 increase in PM2.5 was 1.01 (95% confidence interval (CI): 0.98–1.04). The adjusted odds ratio for a 5 μg m −3 increase in NO2 was 1.03 (95% CI: 0.98–1.08). In subgroup analyses, larger associations for NO2 were observed among past smokers (OR 1.11 (95% CI: 1.02–1.20) per 5 μg m −3 increase). Conclusions: Overall, we found limited evidence of associations between long-term exposure to NO2 or PM2.5 and PD. The associations observed among past smokers require further corroboration. Highlights: NO2 and PM2.5 were weakly associated with self-reported physician-diagnosed Parkinson's disease. The association was stronger with NO2 than PM2.5 The association with NO2 was statistically significant in past smokers.